A Bis‐Triazacyclononane Tris‐Pyridyl N9‐Azacryptand "Beer Can" Receptor for Complexation of Alkali Metal and Lead(II) Cations. Issue 41 (19th June 2018) - Brown, Asha; Bunchuay, Thanthapatra; Crane, Christopher G.; White, Nicholas G.; Thompson, Amber L.; Beer, Paul D.
Abstract: A new bis‐triazacyclononane tris‐pyridyl N9 ‐azacryptand ligand is prepared via a convenient one‐pot [2+3] condensation reaction between triazacyclononane and 2, 6‐bis(bromomethyl) pyridine in the presence of M2 CO3 (M=Li, Na, K). The proton, lithium, sodium, potassium and lead(II) complexes of the ligand are characterised in the solid state. Preliminary solution‐phase competition experiments indicate that the cryptand ligand preferentially binds lead(II) in the presence of sodium, calcium, potassium and zinc cations in methanol solution. Abstract : Not just a tin can : A new N9 ‐azacryptand "Beer Can" receptor for metal cations is prepared by a convenient one‐pot [2+3] condensation reaction which is templated by alkali metal cations.